Proliferative effect of the calcium channel blocker Nifedipine on human embryonic kidney cells - Ahmad, Jamil L.; Okebaram, Chukwudi C.; Ogbuagu, Emmanuel O.; Ogbonnaya, Chidozie N.; Asobie, Geoffrey C. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Numerous epidemiological studies have shown a positive as well as negative association between chronic use of calcium channel blockers and the increased risk of developing cancer. However, these associations were enmeshed with controversies in the absence of laboratory based studies to back up those claims. The aim was to determine in mechanistic terms the association between the long-term administrations of nifedipineand increased risk of developing cancer with the aid of human embryonic kidney (HEK293) cell line. Methods: Cell counting using the Trypan blue dye exclusion and 3-[4, 5-Dimethylthiazol-2-yl]-2, 5-diphenyl-tetrazolium bromide (MTT) assays were used to investigate the effect of nifedipine on the growth pattern of HEK293 cells. Results: Nifedipine had a proliferative effect on HEK293 cells growth and this proliferation is more profound at low concentrations of nifedipine than high concentrations and the proliferation was statistically significant (p<0.01). Conclusions: The chronic use of nifedipine is associated with increased proliferation of cells with concomitant elevation of polyamines concentration and elevated polyamine levels have been implicated in many malignant transformations and hence, these provide possible explanation on the link between long term use of nifedipine and development of some human cancers.